From Agriculture to Nutrition : Pathways, Synergies and Outcomes - World Bank (Washington, DC, 2017)
The report seeks to analyze what has been learned about how agricultural interventions influence nutrition outcomes in low-and middle-income countries, focusing on the target populations of the millennium development goals-people living on less than a dollar a day. It also sets out to synthesize lessons from past efforts to improve the synergies between agriculture and nutrition outcomes. The report identifies a number of developments in agriculture and nutrition that have transformed the context in which nutrition is affected by agriculture. The relationship between agriculture and human nutrition is far more complex than the relationship between food production and food consumption or the economic relationship between food supply and food demand. Expanding agriculture's purview and capacity to embrace those contributing factors and determinants of nutrition that are traditionally the province of other disciplines or improving agriculture's interface with other, nonagricultural sectors, suggest themselves as possible ways forward. The limitations of production-focused agricultural programs and interventions in delivering improved nutrition impacts have been recognized by some in the agricultural community for decades. In the early 1980s a number of international development agencies undertook programs that sought to orient agricultural production to nutrition-related objectives, and over time a substantial body of literature developed around the analysis of the programs' results.